2021
DOI: 10.1007/s10140-021-01928-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on the activity of the Radiological Emergency Department: the experience of the Maggiore della Carità Hospital in Novara

Abstract: Purpose During the first peak of the COVID-19 pandemic, the activity of Emergency Departments worldwide changed dramatically, focusing on diagnosis and care of the Sars-Cov-2 associated disease. These major changes also involved the activity of the Emergency Radiology Department (ERD). This study aimed to analyse the impact of the COVID-19 pandemic on imaging studies, both in terms of the amount, frequency and subspecialty of different imaging modalities requested to the ERD of the Maggiore della… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
(6 reference statements)
2
2
0
Order By: Relevance
“…Naidich et al [13] showed that chest CT angiography increased among inpatients in a large healthcare system in the US in the first 16 weeks of 2020. Increased chest CT use in accordance with the local epidemic spreading was also reported in French [14] and Italian [16] radiological centers and by other authors in Brazil [15] . The increased use of chest CT during the COVID-19 pandemic is not unforeseen as the severe forms of the disease are largely associated to the extent of pulmonary involvement and chest CT has a recognized role in assessing severity and progression of the disease.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Naidich et al [13] showed that chest CT angiography increased among inpatients in a large healthcare system in the US in the first 16 weeks of 2020. Increased chest CT use in accordance with the local epidemic spreading was also reported in French [14] and Italian [16] radiological centers and by other authors in Brazil [15] . The increased use of chest CT during the COVID-19 pandemic is not unforeseen as the severe forms of the disease are largely associated to the extent of pulmonary involvement and chest CT has a recognized role in assessing severity and progression of the disease.…”
Section: Discussionsupporting
confidence: 79%
“…Mammography, nuclear medicine, and magnetic resonance imaging were among the most affected modalities [10] , [11] , [12] . Nevertheless, the use of imaging examinations for the diagnosis and management of COVID-19, particularly chest computed tomography (CT) increased [13] , [14] , [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was not easy to apply ultrasound due to problems associated with wearing personal protective equipment before and after the POCUS scan, as well as disinfection of machines. Although many studies have recommended the use of lung ultrasound in the COVID-19 pandemic [38][39][40], the use of ultrasound has significantly reduced in our institution, as reported in other studies [41,42].…”
Section: Discussionsupporting
confidence: 52%
“…Several recently published studies have shown fewer ED visits for matters unrelated to COVID-19 since the pandemic began, likely owing to initial mobility restrictions and fear of contagion. 3,13 However, the greatest reduction in ED visits was seen during the early portion of the pandemic, 14 when most elective surgical procedures were also paused by government mandate, making it unclear how large a confounding factor this would be for our particular study. Therefore, our results showing fewer ED visits and readmissions could be attributable to the initial fear of going to the hospital.…”
Section: Discussionmentioning
confidence: 92%